Climate and weather in basic education: Didactic experience of observation and gathering of data with the use of thermohygrometer and pluviometer (Revista Contexto & Educação, 2024)
The activity of collecting primary data in a school environment is an important exercise to be promoted on a daily basis, since students have contact with research methodology on reality. Content related to climate in Geography and School Biology should establish the relationship between climatic and meteorological phenomena and their influence on student learning. In this way, the collection of data in practice, related to the physical and social elements addressed in the theory, is placed as important in the teaching of subjects. In this sense, the objective was to survey and analyze the rainfall and temperature in the municipality of Dores do Rio Preto, Espírito Santo, to strengthen the teaching-learning process at school. During the 24-month period (2019-2021), rainwater collections were carried out. For data collection, an analog rainfall and a thermohygrometer were used. The results showed that there are relevant variations during the analyzed months. The climate approach in basic education contributed to the classes of the contents, where students were more interested in studying such contents. In this sense, the work is important for reporting real precipitation values and for allowing the identification of annual rainfall and temperature anomalies.
Keywords: Rainfall; Precipitation; Teaching; Climate